Detecting centennial changes in the clarity and colour of the Red and Eastern Mediterranean Seas by retracing the “Pola” expeditions - Jonathan R. Heath; Robert J. W. Brewin; Jaime Pitarch; Dionysios E. Raitsos (Frontiers in Marine Science)
The world’s oceans and seas are changing rapidly due to several natural and anthropogenic reasons. Among these, the largest and likely most threatening to marine life being the climate crisis and rising sea temperatures. Studying the dominant primary producers of most marine ecosystems, phytoplankton, and their response to these alterations is challenging, yet essential due to the critical role phytoplankton play in both the oceans and wider biosphere. Satellites are a crucial tool used to study phytoplankton but lack the timespan needed to accurately observe abundance patterns in response to climate change. Historical oceanographic data are increasingly being used to understand changes in the abundance of phytoplankton over the last century. Here, we retrace Secchi depth and Forel-Ule colour scale surveys performed during the “Pola” expeditions between 1890-1898 using contemporary satellite data, to assess changes in water colour and clarity (and by extension phytoplankton abundance) in the Red Sea and the Eastern Mediterranean Sea over the past century. The results show a significant greening of both regions investigated as well as a decrease in water clarity. The Red Sea Forel-Ule colour increased by 0.83 (± 0.08) with an average decrease in Secchi depth of 5.07 m (± 0.44). The Forel-Ule colour in the Eastern Mediterranean increased by 0.50 (± 0.07) and the historic Secchi depth readings were an average of 8.85 m (± 0.47) deeper than present day. Changes in Secchi depth between periods were greater than that which may have been caused by differences in the size of the Secchi disk used on the “Pola” expeditions, estimated using traditional Secchi depth theory. There was no clear change in seasonality of phytoplankton abundance and blooms, although winter months saw many of the largest changes in both measured variables. We discuss potential drivers for this change and the challenges and limitations of combining historical and modern datasets of water clarity and colour.